Upaya Pencegahan Komplikasi Infeksi pada Penggunaan Central Venous Catheter (CVC) - Septiana Fathonah; Tri Wahyu Murni (Jurnal Keperawatan Notokusumo, 2014)
Critically-ill patients at intensive care unit (ICU) require hemodinamic monitoring such as CVP (Central Venous Pressure) monitoring using CVC (Central Venous Catheter). CVC insertion is associated with several complications for the patients. One of them is catheter-related infections which further expose the patients for a higher risk of morbidity and mortality. CVC could be contaminated via extra and intraluminal route which result in systemic spreading of the microorganism and cause blood stream infection (BSI). Health care personnel must actively perform prevention measures to lower the infection risk. Since the infections could be due to migration of the microorganism at insertion site, a proper dressing method plays an essential role to prevent the infections as an effective barrier for the microorganisms. In this review, we will first discuss the prevention measures in general. Finally, we discuss the advantegous and disadvantegous of using two types of dressing methods (transparent polyurethane and gauze and tape dressing).